Physicochemical and Antioxidant Properties of Chitosan Films Incorporated with Cinnamon Oil - Marco A. López-Mata; Saul Ruiz-Cruz; Norma Patricia Silva-Beltrán; José de Jesús Ornelas-Paz; Víctor Manuel Ocaño-Higuera; Francisco Rodríguez-Félix; Luis A. Cira-Chávez; C. L. Del-Toro-Sánchez; Keiko Shirai (International Journal of Polymer Science)
Chitosan films (CF) with cinnamon bark oil (CO) incorporated at 0% (control), 0.25%, 0.5%, and 1.0% v/v were prepared by an emulsion method. The films were characterized based on their physical properties (solubility, water vapor permeability, optical property, and microstructure) and antioxidant properties (DPPH, ABTS, and its protective effects on human erythrocytes). The results showed that the incorporation of 0.5 and 1.0% of CO into the CF significantly decreased its solubility to 22% of the control (p<0.05). The water vapor permeability of the CF-CO was significantly reduced to 40% with low concentrations of CO (0.25%) incorporated into the CF. In general, the films presented a yellow coloration and an increase in transparency with the incorporation of CO into the CF. It was also observed that the incorporation of CO increased the antioxidant activity between 6.0-fold and 14.5-fold compared to the control, and the protective capacity against erythrocyte hemolysis increased by as much as 80%.